PENERAPAN MODEL KOOPERATIF TIPE STAD BERBANTUAN GENIALLY PADA MATERI PENERAPAN NORMA DALAM KEHIDUPAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V UPTD SDI NUNBAUN DELHA - Chendy Rizmawan, Yosef; Martha Khristina Kota; Rista Apriliya Devi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research entitled Application of Genially Assisted STAD Type Cooperative Model on the Material of Application of Norms in Life to Improve the Learning Outcomes of Fifth Grade Students of UPTD SDI Nunbaun Delha is motivated by the low learning outcomes of fifth grade students of UPTD SDI Nunbaun Delha. This was obtained from the results of initial observations conducted by researchers during PLP activities in fifth grade of UPTD SDI Nunbaun Delha, found conditions related to the learning outcomes of fifth grade students in Pancasila Education learning. Of the 25 students, 28% or 7 students met the KKTP set by the school, while 72% or 18 other students had not met the KKTP. This study uses a Classroom Action Research (CAR) approach consisting of planning, implementation, observation and reflection stages. The data collection techniques used are observation and tests using research instruments including teacher observation sheets, student observation sheets, test questions, and documentation studies. The data analysis technique used is descriptive qualitative with percentage calculations (%). In cycle I, the percentage of students achieving mastery was 52%, falling into the